2015
DOI: 10.1080/17461391.2015.1023221
|View full text |Cite
|
Sign up to set email alerts
|

Sleep, anxiety and electronic device use by athletes in the training and competition environments

Abstract: This study subjectively assessed sleep quality and quantity, state anxiety and electronic device use during a 7-day training week (TRAIN) and a 7-day competitive tournament (COMP). Eight state-level netball players used wrist-watch actigraphy to provide indirect sleep measures of bedtime, wake time, sleep duration, sleep onset latency, sleep efficiency, wake after sleep onset and fragmentation index. State anxiety was reported using the anxiety sub-scale in the Profile of Mood States-Adolescents. Before bed du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 28 publications
1
42
1
1
Order By: Relevance
“…In judo competitors, the use of electronic devices during a training camp had no effect on TST or SE,13 while in netballers no significant association between duration of electronic device use and subsequent sleep outcomes was found during either training or competition 61…”
Section: Resultsmentioning
confidence: 80%
“…In judo competitors, the use of electronic devices during a training camp had no effect on TST or SE,13 while in netballers no significant association between duration of electronic device use and subsequent sleep outcomes was found during either training or competition 61…”
Section: Resultsmentioning
confidence: 80%
“…Two studies, however, reported a significant increase in pre-competition total sleep time [39, 40], while one study [52] reported a significant increase in sleep efficiency. Again, however, there was evidence of sleep–performance relationships.…”
Section: Resultsmentioning
confidence: 99%
“…In this respect, future studies may also investigate if sleep requirements differ according to playing position and/or individual activity performed during the match. As it has been proposed that sleep parameters may be affected as a result of a greater need for recovery sleep due to more demanding workloads [44], it may be hypothesised that players in a more 'physically' demanding position (i.e. fullbacks, midfielders and forwards [45,46]) may exhibit positional differences in sleeping patterns compared with goalkeepers and central defenders.…”
Section: High-intensity Exercise and Sleepmentioning
confidence: 99%